2005
DOI: 10.1080/09637480500195066
|View full text |Cite
|
Sign up to set email alerts
|

Six reasons why the waist-to-height ratio is a rapid and effective global indicator for health risks of obesity and how its use could simplify the international public health message on obesity

Abstract: We suggest that a simple, rapid screening tool-the waist-to-height ratio (WHTR)-could help to overcome debates about the use of different body mass index (BMI) boundary values for assessing health risks in different populations. There are six reasons for our proposal: WHTR is more sensitive than BMI as an early warning of health risks. WHTR is cheaper and easier to measure and calculate than BMI. A boundary value of WHTR = 0.5 indicates increased risk for men and women. A boundary value of WHTR = 0.5 indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
717
5
59

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 819 publications
(829 citation statements)
references
References 18 publications
20
717
5
59
Order By: Relevance
“…WHtR has received considerable interest, and the results suggest keeping one's waist to less than half one's height25, 26, 27. A Chinese study reported that waist‐to‐stature ratio (or saying WHtR) is the best simple anthropometric indicator in predicting a wide range of cardiovascular risk factors and related health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…WHtR has received considerable interest, and the results suggest keeping one's waist to less than half one's height25, 26, 27. A Chinese study reported that waist‐to‐stature ratio (or saying WHtR) is the best simple anthropometric indicator in predicting a wide range of cardiovascular risk factors and related health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has found that the WHtR, rather than BMI and WC, was more strongly correlated with cardiovascular comorbidities and was better at predicting the metabolic syndrome in adults and cardiovascular health risks, such as high BP and high blood lipids, in adults and children (18,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a cut-off of 0?5 is suitable to apply to children and adolescents, independent of age and sex. Although we have previously shown that this index is a statistically acceptable index for use in children and adolescents (19) , the sensitivity of using a cut-off of 0?5 to identify abdominal obesity or risk of CVD in children and adolescents has not been investigated (18,(20)(21)(22)(23)(24)(25)28,29) .…”
mentioning
confidence: 99%
“…The present study has confirmed that WC was comparable to WHpR and WHtR in association with cardiovascular risk factors, although some studies have shown WC is better associated with cardiovascular risk factors and outcome when compared to WHpR 3,26-28 and some studies advocate WHtR as a better indicator. 8,29 However, further prospective cohort studies need to be conducted to determine the association of these obesity indices with cardiovascular risk factors and their optimal cutoff points. For public health stand point, waist measurement could be a simple index for public as a self-monitoring measurement because it is relatively simpler and easier to measure and interpret as compared to BMI and others.…”
Section: Discussionmentioning
confidence: 99%